2018
DOI: 10.1088/1367-2630/aae7f0
|View full text |Cite
|
Sign up to set email alerts
|

Si-atoms substitutions effects on the electronic and optical properties of coronene and ovalene

Abstract: We report a computational comparative study of the ground and excited states properties of graphene nanoribbons, analyzing the case of coronene (C 24 H 12 ) and ovalene (C 32 H 14 ) and their silicon-atoms substituted counterparts with single, double and triple atomic insertions. We used density functional theory (DFT) and time-dependent DFT to quantify the effects on the electronic and optical properties as a result of the chemical modifications. In particular, we compared ground-state total energies, electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…We checked the basis set convergence by adopting the Aug-cc-pVTZ (augmented, polarized triple-ζ) basis set, but it turned out that the Aug-cc-pVDZ basis already provides a very good agreement with experiments. We would like to point out that, in previous calculations on other molecular systems carried by some of us, , it had been found that using the B3LYP XC functional , and the 6–31+G*basis set was sufficient to obtain relaxed structures in good agreement with the corresponding experimental data, in particular for the eumelanin related precursors (DHI) and protomolecules. ,, In contrast, we find here that for systems like the tetrameric molecules of eumelanin such a level of theory (in terms of XC functional and basis set) leads to rather unsatisfactory results.…”
Section: Methodssupporting
confidence: 61%
“…We checked the basis set convergence by adopting the Aug-cc-pVTZ (augmented, polarized triple-ζ) basis set, but it turned out that the Aug-cc-pVDZ basis already provides a very good agreement with experiments. We would like to point out that, in previous calculations on other molecular systems carried by some of us, , it had been found that using the B3LYP XC functional , and the 6–31+G*basis set was sufficient to obtain relaxed structures in good agreement with the corresponding experimental data, in particular for the eumelanin related precursors (DHI) and protomolecules. ,, In contrast, we find here that for systems like the tetrameric molecules of eumelanin such a level of theory (in terms of XC functional and basis set) leads to rather unsatisfactory results.…”
Section: Methodssupporting
confidence: 61%
“…In fact, the ΔSCF technique enables us to calculate the fundamental gap for each cluster. From the ΔSCF method, one obtains the quasiparticle gap (or fundamental gap) by the expression , …”
Section: Results and Discussionmentioning
confidence: 99%
“…With respect to the exchange-correlation (XC) potential, we chose the B3LYP one since with respect to other possibilities, e.g., the Perdew–Burke–Ernzerhof (PBE) functional, it reproduces better results for different clusters, e.g., for many PAH molecules, for both ground and excited states, as previously established. …”
Section: Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…60,61 The chosen basis-set is composed by a valence double- ζ set including d polarization functions (indicated with the symbol “*”) and diffuse functions (“+”) for each atom other than H. The selected couple of XC potential and basis-set has been successfully tested for many different atomic systems, both organic and inorganic, with different sizes and degrees of complexity. 62–77 Moreover, in several works (which studied nanostructures similar to ours) 6,9,41,51,78 the B3LYP XC functional or the 6-31+G* basis-set have been used.…”
Section: Computational Detailsmentioning
confidence: 99%